Exploring Lexemic Idiomatic Expressions in Robert Their’s Wattpad Novel “Storm and Silence” - Surbakti, Tiara Sari; Pasaribu, Arsen Nahum; Sembiring, Rony Arahta (IKIP Siliwangi, 2025)
This research explores the use of lexemic idiomatic expressions in Robert Thier's Wattpad novel